THE EFFECTIVENESS OF THE N5-N4 ACCELERATION INTENSIVE CLASS LEARNING METHOD AT OHM STUDI JEPANG - Hardianto Rahardjo; Mira Kurniawati (WIDAI Japanese Journal, 2021)
The increasing interest in working or continuing to studi in Japan requires Japanese language skills at least JLPT N4. Thus the authors are interested in examining whether intensive study for 3 months is effective enough to achieve JLPT N4. PT OHM Studi Jepang is a consulting and document management service company for work and school in Japan, by facilitating intensive classes to help participants pass JLPT N4. This study descusses the effectiveness of the learning method applied in accelerated intensive class N5-N4 to 18 students who are the subject of research by the author. The data obtained is the value of several test and the results of interviews with respondents which were processed using quantitative descriptive methods to produce two conclusions which are, how effective is the learning method in the N5-N4 OHM accelerated intensive class, and what needs to be addressed to increase the effectiveness of learning in the accelerated intensive class N5-N4 OHM. This research and the results will hopefully be useful to broaden the readers knowledge about effective Japanese teaching methods